Auntie Anne : my story - Beiler, Anne, 1949-; Stoltzfus, Freiman, ill. (Gap, PA : Auntie Anne's, Inc. Publications, 2002)
Auntie Anne is the story of a girl who grows up in Pennsylvania's Amish country, and how a simple, unique pretzel recipe gives her life an unexpected twist.
Keywords: Beiler, Anne, -- 1949-; Auntie Anne's Incorporated -- History; Success in business -- Biography; Franchises (Retail trade) -- United States -- History; Amish -- Social life and customs